THE BELIEF WORSHIP OF “THANH HOANG” AND THE WORSHIP OF “MAU” OF THE PEOPLE IN AN LAC, LONG THINH AND VAN LAI DURING THE MEDIEVAL PERIOD THROUGH “HAN NOM” DOCUMENTS - Nguyen Thanh Hoa; Mai Phuong Ngoc (Tạp chí Khoa học)
The villages of An Lac, Long Thinh and Van Lai, now part of Thuan Minh commune (Tho Xuan district, Thanh Hoa province), are an ancient land located on the left bank of Luong Giang (Chu river) in the space of “Lam Son huong”, the cradle of the early Le dynasty, where the Le Trung Hung dynasty's palace was located when the country was in the South-North dynasties. The villages here have an early formation history, so the traditional culture, including the people's religious life in Thuan Minh villages, bears prominent marks. Based on Han Nom documents related to the villages in Thuan Minh, the article focuses on researching the imprints of Thanh Hoang and Mau worship beliefs of the people of the three villages of Van Lai, An Lac and Long Thinh in the medieval period, thereby clarifying the spiritual and cultural values of the people of Thuan Minh.